Análise experimental de vigas de concreto armado submetidas a carregamento prévio e reforçadas à flexão com compósitos reforçados com fibra de carbono - Santos, Juliane da Costa (2019)
Concrete is a material widely applicable in structures all over the world. Therefore, its deterioration and problems caused over time are inevitable. Considering this fact, the structures of concrete recovery is a real need. There are numerous techniques structural recover and repair. The system using carbon fibre reinforced polymer (CFRP) is among them. CFRP is lightweight, presents high tensile strength and is easy to be installed. This research presents an experimental analysis about the monotonic flexural behaviour and ultimate capacity of ten reinforced concrete beams partially damaged and cracked after preloading in flexure. The beams were externally repaired using one or two layers of CFRP fabrics and bonded with epoxy resin over a pre-treated substrate aiming better adhesion. Each beam was loaded and tested by a flexural tensile strength in four points bending test. The ultimate load and maximum deflection were recorded. The aim of this study was to verify the effectiveness of the CRFP as reinforcement of the damaged structure of reinforced concrete. It was observed that specimens reinforced with one layer of CRFP increased, in average, 49,70% of the tensile strength while using two layers improved it in 56,66% when compared to the control beams with no additional external reinforcement. When analysing the actual behaviour of the CRFP reinforced beams with the designed, it was observed an average achievement 4,65% less than the expected for the group using one layer and 5,05% less with 2 layers of CRFP. Therefore, the accuracy of the results was satisfactory when compared to the project presented by Pivatto (2017). During the structural analysis, it was observed that the shear force caused the failure of the beams. Additionally, it was verified the effectiveness of the CFRP when used as an external reinforcement to recover the damaged structures of reinforced concrete studied, submitted to their peak flexural tensile strength.